Analyzing the Use of Evidence in Grade 11 Learners’ Position Papers - Lorenzo, Abigail (Journal of Interdisciplinary Perspectives, 2025)
The study analyzed the use of evidence-based statements by Grade 11 learners in their position papers. Employing a quantitative content analysis method, the study assessed the proficiency of 133 participants in terms of evidence use using an adapted rubric. Hemberger’s (2017) classification of functional evidence-based statements was used for analysis. Findings revealed that the majority of the grade 11 learners were still Developing in terms of their evidence-use proficiency. Moreover, "Support My Own (M+)" evidence-based statements were used most frequently, while "Weaken My Own (M-)" statements were used least commonly. Lastly, there is a statistically significant difference in the use of Support My Own, Weaken Other, and Support Other evidence-based statements across proficiency levels. The study concluded that as writers' proficiency increases, they improve in incorporating and articulating evidence to support their assertions. It recommends developing instructional materials that focus on scaffolding, such as graphic organizers to help students outline their text, peer review sessions to practice providing constructive feedback, which can be applied to their evidence interpretation when writing, and writing tasks that require critical analysis, such as literature review projects. Future research should explore intervention strategies to address identified challenges.